Some Simple Economics of the Blockchain: Blockchain technology can shape innovation and competition in digital platforms, but under what conditions? - CATALINI, CHRISTIAN; GANS, JOSHUA S. (Communications of the ACM, 2020)
The article discusses how blockchain technology identifies the cost of networking and verification, which can impact competition and technological innovation. It discusses Bitcoin blockchain, the economics of digitization and technological change, and how blockchain technology can prevent data leaks.